(untitled) (Journal of Patan Academy of Health Sciences, 2020)
It is important to track the changing case definition to plan for the clinical response. Transmission pattern of disease have been changing in COVID-19. Countries with no reported cases have moved on to sporadic, cluster of cases and then to community transmission. The response depends on how rapidly the transmission is changing in the country.